2016
DOI: 10.1002/ird.2068
|View full text |Cite
|
Sign up to set email alerts
|

NPS Pollution Reduction from Alpine Fields using Surface Cover Material and Soil Amendments

Abstract: We described the effects of straw mat cover and soil amendments on runoff, agricultural non-point source nNPS) pollution and crop yield on sloping alpine fields in Korea. Two sandy loam field plots were prepared. One was a control plot and the other (SPG) was an experimental plot treated with rice straw, polyacrylamide (PAM) and gypsum (rice straw mat (3,300 kg/ha) + PAM (5 kg/ha) + gypsum (1 ton/ha)). Chinese cabbage was cultivated in the plots and seven rainfall-runoff events were monitored during the growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…This top layer of soil often contains higher levels of nutrients compared to deeper layers for depths of 10-20 and 20-30 cm centimetres (Yue et al, 2015). In this study, we found that the CS and MS addition treatments increased the TOC, TN, MBC and TCS content in upper 10 cm soil (Figures 3 and 5), which was consistent with Won et al (2016). These results could be attributed to the abundant C content of CS and MS treatments, hence increasing the soil TOC after their use.…”
Section: Response Of Soil Fertility Promotion Under Different Soil Am...supporting
confidence: 86%
See 3 more Smart Citations
“…This top layer of soil often contains higher levels of nutrients compared to deeper layers for depths of 10-20 and 20-30 cm centimetres (Yue et al, 2015). In this study, we found that the CS and MS addition treatments increased the TOC, TN, MBC and TCS content in upper 10 cm soil (Figures 3 and 5), which was consistent with Won et al (2016). These results could be attributed to the abundant C content of CS and MS treatments, hence increasing the soil TOC after their use.…”
Section: Response Of Soil Fertility Promotion Under Different Soil Am...supporting
confidence: 86%
“…Additionally, soil amendments are effective in increasing SOC (soil organic carbon), improving soil aggregates and altering SD (Soil bulk density) (Baiamonte et al, 2019;Xu et al, 2015). Previous research has explored the potential benefits of soil amendments, including organic materials and straw, in enhancing soil fertility and increasing levels of soil carbon and nitrogen, promoting soil aggregate formation and altering microbial community structure to support plant growth (Li et al, 2020;Won et al, 2016;Zhang, Zhang, & Chang, 2023). Dai et al (2020) showed that plant productivity could be increased by more than 16% regardless of the type of soil amendment and soil status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, land covers and soil amendments such as biochar, which enhance the soil structure and porosity, are used to protect the soil [47,48]. Won et al used rice straw, polyacrylamide, and gypsum to treat with Chinese cabbage filed, which resulted in reduction of suspended solids and of total nitrogen (TN) by 86.6% and 34.7%, respectively [49]. Lee et al have studied the effects of soil amendments on soil loss [50].…”
Section: Conservation Tillagementioning
confidence: 99%